Digital Discourses on Medical Tourism: How Indonesians Consider Visiting Penang for Healthcare – A Netnographic Study on Twitter - Niyu Niyu; Uud Wahyudin (LONTAR: Jurnal Ilmu Komunikasi, 2025)
The phenomenon of medical tourism from Indonesia to Penang, Malaysia, has continued to show a significant upward trend in recent years. In today's digital era, social media platforms such as X (formerly Twitter) have become active public discussion arenas, places where netizens share experiences, provide recommendations, and even consider decisions to undergo treatment abroad. This study aims to explore how digital narratives related to the practice of seeking medical treatment in Penang are formed, spread, and negotiated by Indonesians on the X platform. Using a netnography approach, this study analyzes tweets containing keywords related to treatment in Penang, revealing the dynamics of conversations in various discussions in the digital space. The results of the analysis identified four main themes that dominated the conversation: (1) ease of access and convenience of services; (2) exchange of information and recommendations between users; (3) crisis of trust in domestic health services; and (4) considerations of price, quality, and added value offered by services in Penang. These findings indicate that the decision to seek medical treatment abroad is not only influenced by medical needs or individual preferences, but also by social constructions formed in the digital space. Social media plays an important role as an e-WOM (electronic word of mouth) channel that shapes public perception and preferences for cross-country health services. This research is expected to contribute to the development of health communication and digital culture studies, as well as being a basis for thinking about managing information and health service reputation more strategically in the era of social media.